Visualization of heat flow using Bejan's heatline due to natural convection of water near 4 °C in thick walled porous cavity - Varol, Yasin; Öztop, Hakan Fehmi; Mobedi, Moghtada; Pop, Ioan (Pergamon-Elsevier Science Ltd, 2010)
A numerical study oil natural convection heat transfer of cold water near 4 degrees C in a thick bottom walled cavity filled with a porous medium has been performed. It is assumed that the cavity is isothermally heated from the Outside of the thick bottom wall and cooled from ceiling The finite-difference method has been used to solve the governing partial differential equations of heat and fluid flow. Effects of thermal conductivity ratio. Rayleigh number and bottom wall thickness on heat transfer from the bottom to the ceding have been studied. The heatline visualization technique has been used to demonstrate the path of heat transport through the enclosure. Moreover, streamlines and isotherms have been used to present fluid now and temperature distributions. The obtained results show that multiple circulation cells are formed in the cavity and the local Nusselt numbers at the bottom wall and solid-fluid interface are highly affected by formed cells. The increase of Rayleigh number and thermal conductivity ratio increases heat transfer through the cavity. However. the increase of thickness of the bottom wall reduces the mean Nusselt number. Almost one-dimensional conduction heat transfer is observed in the solid bottom wall of the cavity. (C) 2010 Elsevier Ltd. All rights reserved
Keywords: Heatline; Maximum density; Conjugate; Natural convection